Cost and Time Control Using The Earned Value Concept (EVM) Method : Case Study of Ahmad Dahlan Hospital Development Project, Kediri - Rini Pebri Utari; Sandi Wahyudiono; Andi Saiful Amal; Langgeng Ardian (G-Tech: Jurnal Teknologi Terapan, 2025)
Time delays and cost overruns are frequent problems in construction projects. To evaluate these issues, this study applies the Earned Value Management (EVM) method to assess cost and schedule performance in the Muhammadiyah Ahmad Dahlan Hospital project in Kediri. The analysis focuses on three key indicators—Budgeted Cost of Work Performed (BCWP), Budgeted Cost of Work Scheduled (BCWS), and Actual Cost of Work Performed (ACWP)—evaluated during weeks 10, 17, and 32. Results show that in week 10, project performance indicated delays and cost overruns (CPI = 0.75; SPI = 0.97). In week 17, the schedule improved (SPI = 1.50) but cost performance remained inefficient (CPI = 0.996). By week 32, both indices were positive (CPI = 1.011; SPI = 1.03), showing that the project finished earlier and more efficiently. The Budget Estimate at Completion (BEAC) was IDR 57,919,253,725, with an estimated duration of 39.79 weeks, slightly faster than planned. This study contributes to enhancing project efficiency evaluation through periodic EVM analysis, providing insights for better cost and time control in construction management.